Bayesian instrumental variables and simultaneity - Rossi, Peter (Henry Stewart Talks, 2010)
Simultaneity and the marketing mix, Conditional likelihood, Instrumental variables, The linear case, Identification, Priors, Gibbs sampler, Non-random marketing mix Variables, The sales force allocation problem, NBD regression, The marginal distribution of X, The full model